School Dictionaries for First-Language Learners - Tarp, Sven; Gouws, Rufus H. (Lexikos, 2012)
Acknowledging the ambiguity of terms like school dictionary, children's dictionary, first language, mother-tongue this article motivates a specific use of school dictionary, first language and learner and focuses on various problems in these dictionaries. The typical functions of these dictionaries are discussed with reference to the lexicographic needs of first-language learners. Looking at a few existing dictionaries, suggestions are made for the inclusion and presentation of certain data types. The importance of the use of natural language in the paraphrases of meaning is discussed. It is emphasised that lexicographers should consult teachers and curriculum experts when planning school dictionaries and that the grade and age of the target user needs to be taken into account. The aim of this article is not to give final solutions to the questions raised but merely to recommend that a number of factors — or variables — are taken into account when planning future school dictionaries. In this respect, a number of questions are formulated that need to be answered when planning the compilation of school dictionaries.